Predictors of subsequent myocardial infarction, stroke, and death in stable post-myocardial infarction patients: A nationwide cohort study. Issue 7 (1st October 2019) - Chen, Dong-Yi; Li, Chen-Yu; Hsieh, Ming-Jer; Chen, Chun-Chi; Hsieh, I-Chang; Chen, Tien-Hsing; Chen, Shao-Wei; Wang, Chao-Yung; Chang, Shang-Hung; Lee, Cheng-Hung; Tsai, Ming-Lung; Ho, Ming-Yun; et al.
Abstract: Background: This study investigated the predictors of subsequent cardiovascular events in stable post-myocardial infarction patients in Taiwan. Methods: A total of 11, 183 patients were recruited who had survived one year post-myocardial infarction without subsequent events of recurrent myocardial infarction or stroke from the Taiwan National Health Insurance Research Database. Their composite cardiovascular event rates were identified. Results: The composite cardiovascular events rate in three year follow-up in the post-myocardial infarction population was 13.8%. Corresponding event rates were 5.8% recurrent myocardial infarction, 5.0% stroke, and 5.2% death. Independent factors associated with a higher risk of ischemic events or death included heart failure (hazard ratio (HR)=1.19), hypertension (HR=1.16), age (65–75 vs <65 years: HR=1.29; 75–85 vs <65 years: HR=1.50; >85 vs <65 years: HR=1.70), diabetes (HR=1.33), prior stroke (HR=1.24), chronic kidney disease (HR=1.4), atrial fibrillation (HR=1.27), and underutilization of guideline-based medication (HR=1.73). Composite risk for myocardial infarction, stroke and death increased progressively from 4.9% in patients with zero risk factor to 100.0% in patients with eight risk factors. Conclusions: For acute myocardial infarction patients surviving one year without subsequent events of recurrent myocardial infarction or stroke, the risk of cardiovascular events remained high. Eight predictors identified patients at increased risk for subsequent cardiovascular events within the next three years. These results suggest an unmet need, particularly in patients with additional risk factors.